Dexamethasone‐Induced Skeletal Muscle Atrophy Increases O‐GlcNAcylation in C2C12 Cells. Issue 8 (2nd February 2016) - Massaccesi, Luca; Goi, Giancarlo; Tringali, Cristina; Barassi, Alessandra; Venerando, Bruno; Papini, Nadia
ABSTRACT: Skeletal muscle atrophy is a well‐known adverse effect of chronic treatment with glucocorticoids and it also occurs when stress conditions such as sepsis and cachexia increase the release of endogenous glucocorticoids. Although the mechanisms of action of these hormones have been elucidated, the possible molecular mechanisms causing atrophy are not yet fully understood. The involvement of the O‐GlcNAcylation process has recently been reported in disuse atrophy. O‐GlcNAcylation, a regulatory post‐translational modification of nuclear and cytoplasmic proteins consists in the attachment of O‐GlcNAc residues on cell proteins and is regulated by two enzymes: O‐GlcNAc‐transferase (OGT) and O‐GlcNAcase (OGA). O‐GlcNAcylation plays a crucial role in many cellular processes and it seems to be related to skeletal muscle physiological function. The aim of this study is to investigate the involvement of O‐GlcNAcylation in glucocorticoid‐induced atrophy by using an "in vitro" model, achieved by treatment of C2C12 with 10 μM dexamethasone for 48 h. In atrophic condition, we observed that O‐GlcNAc levels in cell proteins increased and concomitantly protein phosphorylation on serine and threonine residues decreased. Analysis of OGA expression at mRNA and protein levels showed a reduction in this enzyme in atrophic myotubes, whereas no significant changes of OGT expression were found. Furthermore, inhibition of OGA activity by Thiamet G induced atrophy marker expression. Our current findings suggest that O‐GlcNAcylation is involved in dexamethasone‐induced atrophy. In particular, we propose that the decrease in OGA content causes an excessive and mostly durable level of O‐GlcNAc residues on sarcomeric proteins that might modify their function and stability. J. Cell. Biochem. 117: 1833–1842, 2016. © 2016 Wiley Periodicals, Inc.